A new species of the nasal mite genus Ptilonyssus (Mesostigmata, Rhinonyssidae) from Parus major and first record of Rhinoecius brikinboricus from Asio otus from Denmark - Simon Haarder; Ivan Dimov (Persian Journal of Acarology)
Ptilonyssus holmhanseni n. sp. is described and illustrated from a traffic-killed great tit (Parus major) in Eastern Denmark (Lejre) in April 2023. In addition, Rhinoecius brikinboricus Butenko, 1976, collected from a long-eared owl (Asio otus), is reported for the first time in Denmark and Western Europe.